2017
DOI: 10.1002/jcp.25627
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Signatures at the RUNX2‐P1 and Sp7 Gene Promoters Control Osteogenic Lineage Commitment of Umbilical Cord‐Derived Mesenchymal Stem Cells

Abstract: Wharton's Jelly mesenchymal stem cells (WJ-MSCs) are an attractive potential source of multipotent stem cells for bone tissue replacement therapies. However, the molecular mechanisms involved in their osteogenic conversion are poorly understood. Particularly, epigenetic control operating at the promoter regions of the two master regulators of the osteogenic program, RUNX2/P57 and SP7 has not yet been described in WJ-MSCs. Via quantitative PCR profiling and chromatin immunoprecipitation (ChIP) studies, here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 52 publications
0
38
1
Order By: Relevance
“…We recently established that histone acetylation at the CYP24A1 promoter in osteoblastic cells is hierarchically dominant over other active histone marks during induction of CYP24A1 gene transcription in response to 1,25(OH) 2 D 3 . Surprisingly, here we find that 1,25(OH) 2 D 3 -dependent decrease in H3K27me3 at the CYP24A1 promoter is not accompanied by a significant enrichment in H3K27ac, an epigenetic mark found present at transcriptionally active gene promoters in both osteoblastic and nonosteoblastic cells Rojas et al, 2015;Sepulveda et al, 2017). H3K27me3 and H3K27ac have been found to be mutually exclusive at regulatory genomic regions, although most studies indicate that H3K27ac is preferentially enriched at active enhancer and super-enhancer elements (Weiner et al, 2016).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…We recently established that histone acetylation at the CYP24A1 promoter in osteoblastic cells is hierarchically dominant over other active histone marks during induction of CYP24A1 gene transcription in response to 1,25(OH) 2 D 3 . Surprisingly, here we find that 1,25(OH) 2 D 3 -dependent decrease in H3K27me3 at the CYP24A1 promoter is not accompanied by a significant enrichment in H3K27ac, an epigenetic mark found present at transcriptionally active gene promoters in both osteoblastic and nonosteoblastic cells Rojas et al, 2015;Sepulveda et al, 2017). H3K27me3 and H3K27ac have been found to be mutually exclusive at regulatory genomic regions, although most studies indicate that H3K27ac is preferentially enriched at active enhancer and super-enhancer elements (Weiner et al, 2016).…”
Section: Discussioncontrasting
confidence: 73%
“…The reduction in H3K27me3 (and of Ezh2) at the CYP24A1 promoter that accompanies 1,25(OH) 2 D 3 ‐dependent upregulation of CYP24A1 transcription is not paralleled with a rapid enrichment of the active mark H3K27ac (Figure 1e, left panel), that accompanies active transcription of several mammalian genes and, particularly, active enhancers (Holmqvist & Mannervik, 2013; Nurminen et al, 2018; Sepulveda et al, 2017). As a control, using the same anti‐H3K27ac antibody we confirmed that this mark is found enriched at the Runx2 P1 promoter (Figure 1e, right panel), a bone‐related gene that is strongly active in these cells and is transcriptionally independent of the presence of 1,25(OH) 2 D 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we demonstrated that the RUNX2 P1 promoter does not contain repressive histone marks (H3K9me3 and H3K27me3) in WJ‐MSCs . Moreover, following 48 hours of OD stimulation, significant RUNX2/p57 mRNA can be detected and associated with enrichment of activating histone modifications (H3K4me3 and H3K27Ac) at RUNX2 P1 promoter .…”
Section: Discussionmentioning
confidence: 90%
“…Despite this limited acquisition of the osteoblastic gene expression program in WJ-MSC, late OD hallmarks have been detected in a small percentage of the cell populations by staining methods [32]. This suggest that mid-differentiation markers like increased ALP activity and calcium deposition can be regulated in WJ-MSCs independently of canonical osteogenic factors when these cells are stimulated with OB media [20]. Alternatively, these results may be indicating that there is a small subpopulation of cells within our WJ-MSC primary cultures that are less refractory to upregulate the expression of these osteogenic master regulators in OB growing conditions.…”
Section: Runx2 and Jarid1b During Wj-msc Odmentioning
confidence: 99%
“…These results raise significant concern about using BMP2-treated C2C12 cells as a model to address epigenetic mechanisms controlling the expression of this bone master regulator. Additionally, it was recently shown that the inability to activate Sp7 expression following incubation with well-established osteoblast induction medium represents a critical limitation for using mesenchymal stem cells derived from human umbilical cords as a source of pro-osteogenic cells (67). Therefore, these results, together with results of our analyses using the HDAC inhibitor TSA in uncommitted mesenchymal cells, indicate that the activation of Sp7 gene transcription can be induced in nonosteogenic cells independent of DNA demethylation and nucleosome remodeling at the Sp7 promoter although concomitantly with increased histone acetylation and enhanced RNAPII binding.…”
Section: Discussionmentioning
confidence: 99%